ANALISIS MOTIVASI SISWA DALAM PEMBELAJARAN EKONOMI DI KELAS XI IIS 2 SMA SANTUN UNTAN PONTIANAK - Akfatulilah, Rizvi; Sulistyarini, Sulistyarini; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis purpose of this research is to know the student motivation to learn Economic for class XI IIS 2 SMA Santun Untan pontianak. Metodelogy of this rearch is descriptive metothodology eith qualitative approach. Souces of this research are observation and direct communcation with interview and study documentation wcih is paper. The result of this research show that analysis of student motivation to learn economis for class class XI IIS 2 SMA Santun Untan pontianak have 2 indicatoin: 1)instrinsic learning motivation possessed by students of class XI IIS 2 shows that the desire and itention to succeed lack student motivation for learn economic and the encouragment dan needs, hopes and aspirations of the future in economic learnig. 2) Extrinsic learning motivation of student of class XI IIS 2 shows that intersting activities less motivating student to learn economis as well as from rewards in studing and a conducive learning environment that skill makes students less motivated.   Keywords: Student Motivation, Economic Learning.